Assessment of the sustainability of neglected and underutilised crop species: SUSTLIVES approach - El Bilali, Hamid; Cardone, Gianluigi; Rokka, Susanna; De Falcis, Eleonora; Naino Jika, Abdel Kader; Diawara, Ali Badara; Nouhou, Bassirou; Diadie, Halima; Tarri Aliou , Mahamane; Kiebre, Zakaria; Kabre, Jacques (University of East Sarajevo, 2023)
There are different approaches and frameworks for the assessment of sustainability in agriculture and food systems, but only a few of them focus on crops. This gap is even more evident when it comes to the so-called neglected and underutilised species (NUS). To bridge this gap, the present paper describes an approach for the assessment of the environmental, social and economic sustainability of NUS developed within the project SUSTLIVES (Sustaining and improving local crop patrimony in Burkina Faso and Niger for better lives and ecosystems). The indicators identified through a literature review, based on the Web of Science, have been integrated with other indicators used for sustainability evaluation in the agri-food sector. Based on that, a sustainability assessment approach (list of indicators, evaluation methods and units; scoring system and mode of aggregation of scores; reference crops for the selected NUS) was developed. Then, two workshops were organized in Niamey (January 2023) and Ouagadougou (February 2023) to validate the sustainability assessment approach. The validated sustainability assessment matrix contains 27 indicators divided into different themes covering the three dimensions of sustainability: environmental (environmental integrity, agronomic performance and productivity), social (cultural importance and relevance, nutritional quality and diversity, employment, equity and accessibility) and economic (competitiveness, profitability). A scoring system was proposed for each indicator; from 0 (unsustainable) to 10 (very sustainable) with 5 corresponding to the sustainability benchmark value. Besides sustainability assessment, the developed approach allows selecting the NUS with the highest potential in view of their promotion and the development of their value chains.
Keywords: orphan crop; NUS; indicators; scoring system; sustainability benchmark